Project-based learning in teacher education: A reflection on analysing prospective elementary teachers’ knowledge of math, didactics, and technology - Putra, Zetra Hainul; Alim, Jesi Alexander; Melihayatri, Ningrum; Dahnilsyah; Afrillia, Yesi Martha; Aljarrah, Ayman (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Teacher education programs play a crucial role in equipping prospective teachers with the necessary skills to teach mathematics effectively in elementary schools. However, incorporating mathematical, didactic, and technological knowledge remains a challenge. This study aims to investigate the potential of Project-Based Learning (PjBL) to support the development of prospective elementary teachers’ mathematical, didactic, and technological knowledge. Empowering a qualitative design, this study adapted a didactic engineering approach grounded in the Anthropological Theory of the Didactic (ATD). The participants comprised 28 third-year prospective elementary teachers. Data collection involved project documents, observations, reflective journals, and interviews. The findings indicate notable progress in participants’ capacity to design contextual and visual mathematics tasks; however, their theoretical justification was still limited. Thematic coding of the data explained a paradigm shift towards active and experienced teaching. However, reflections on the pedagogical functions of technological tools remained underdeveloped. The study suggests incorporating theory-based reflection and praxeological analysis into teacher education curricula to enhance prospective teachers’ capacity to apply teaching theories in practice, engage in reflective practice, and adapt to diverse students’ needs.